2022
DOI: 10.3946/kjme.2022.218
|View full text |Cite
|
Sign up to set email alerts
|

Summative program evaluation of a Student-Led Seminar Series in the subject of physiology: an outcome-based study

Abstract: Purpose: Active involvement of students in their learning process is a recommended andragogical approach to increase student engagement. Many new teaching-learning strategies based on active learning have been implemented, but their efficacies to achieve the proposed benefits of attaining knowledge, skills, and attitude have not been evaluated, especially in the field of medical education. We substituted passive learning in the conventional tutorial classes with an active-learning strategy of Student-Led Semin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Over a 4-month period, the effectiveness of the SLSS program was evaluated and statistically significant improvement in student satisfaction and self-perceived increase in knowledge, skills and attitude was reported. 11 In our study, Pathology residents benefited from studentled seminars focused on urinalysis and instrumentation of colorimeters, spectrophotometers, and high-performance liquid chromatography (HPLC). Firstly, taking the lead in preparing and delivering seminars enhanced their understanding of the subject matter as they delved into the details, critically analyzed concepts to synthesize knowledge.…”
Section: Student Led Seminarmentioning
confidence: 99%
“…Over a 4-month period, the effectiveness of the SLSS program was evaluated and statistically significant improvement in student satisfaction and self-perceived increase in knowledge, skills and attitude was reported. 11 In our study, Pathology residents benefited from studentled seminars focused on urinalysis and instrumentation of colorimeters, spectrophotometers, and high-performance liquid chromatography (HPLC). Firstly, taking the lead in preparing and delivering seminars enhanced their understanding of the subject matter as they delved into the details, critically analyzed concepts to synthesize knowledge.…”
Section: Student Led Seminarmentioning
confidence: 99%
“…A study conducted at Medical College, Navi Mumbai, in India showed that students who participated in active learning strategies helped voice their ideas independently. They were more effective in groups and increased their acceptance of the ideas/views presented in the group[28]. Providing constructive feedback in a problem-based learning (PBL) tutorial has been shown to facilitate cognitive and behavioral changes for both the students and tutors during and after the PBL tutorial[29].Learning assessment is an important activity in the learning cycle.…”
mentioning
confidence: 99%